If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + 11n = 3 + 14n Solving 15 + 11n = 3 + 14n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14n' to each side of the equation. 15 + 11n + -14n = 3 + 14n + -14n Combine like terms: 11n + -14n = -3n 15 + -3n = 3 + 14n + -14n Combine like terms: 14n + -14n = 0 15 + -3n = 3 + 0 15 + -3n = 3 Add '-15' to each side of the equation. 15 + -15 + -3n = 3 + -15 Combine like terms: 15 + -15 = 0 0 + -3n = 3 + -15 -3n = 3 + -15 Combine like terms: 3 + -15 = -12 -3n = -12 Divide each side by '-3'. n = 4 Simplifying n = 4
| x+22+x+10+19=11+x | | 9x-2x=70 | | 9a-14=a+2 | | -23-3a=-2a-9 | | factorx^3+8x^2+15x=0 | | 11x+1+9x=21 | | 6x+(3x+7)+(x-3)=180 | | 3x-9=1o | | (17-4y)-4y=17 | | x^2-15x-20=0 | | 11k-k=20 | | logx=2.17417 | | Y+13x=19 | | 6x+3x+7+x-3=180 | | 215=90+(25+8)w | | 11x+1+12=23+1 | | 3(x+2)=1-4(4x+1) | | 8b+3=7b-9 | | -1x-10=1.25+0.25 | | 3x+2+2+x=2x+1 | | F=.5k(d-n) | | 3y-5=-10-4y | | -6(3X+2)-13=6 | | 9(3x+1)=4x-5 | | 73-x=28 | | .2x+3=-17 | | 2x-5(4-x)=7+5x | | -84=-7(6-x) | | 4n+2=-2n-10 | | 264=-27 | | 14=7y-bx | | -9p+3+4p+7p-4p-4p= |